2018
DOI: 10.1002/adfm.201706006
|View full text |Cite
|
Sign up to set email alerts
|

Degenerately Hydrogen Doped Molybdenum Oxide Nanodisks for Ultrasensitive Plasmonic Biosensing

Abstract: Plasmonic biosensors based on noble metals generally suffer from low sensitivities if the perturbation of refractive‐index in the ambient is not significant. By contrast, the features of degenerately doped semiconductors offer new dimensions for plasmonic biosensing, by allowing charge‐based detection. Here, this concept is demonstrated in plasmonic hydrogen doped molybdenum oxides (HxMoO3), with the morphology of 2D nanodisks, using a representative enzymatic glucose sensing model. Based on the ultrahigh capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 73 publications
5
106
0
Order By: Relevance
“…As the concentration of IPA increases, the peak intensity at 532.3 eV associated with the surface oxygen gradually increases for SM7, SM5, and SM3 films, accompanied by a peak shift to 532.6 eV. Particularly for SM5 and SM3 films, the surface oxygen peak intensity becomes much more pronounced than that of lattice oxygen, which indicates that the surfaces of SM5 and SM3 films mainly consist of Mo 5+ —OH bonds induced by the hydroxyl group from IPA, which is responsible for changes in oxidation states in the SM during film formation.…”
Section: Resultsmentioning
confidence: 95%
“…As the concentration of IPA increases, the peak intensity at 532.3 eV associated with the surface oxygen gradually increases for SM7, SM5, and SM3 films, accompanied by a peak shift to 532.6 eV. Particularly for SM5 and SM3 films, the surface oxygen peak intensity becomes much more pronounced than that of lattice oxygen, which indicates that the surfaces of SM5 and SM3 films mainly consist of Mo 5+ —OH bonds induced by the hydroxyl group from IPA, which is responsible for changes in oxidation states in the SM during film formation.…”
Section: Resultsmentioning
confidence: 95%
“…We then further examined the O 1s XPS spectra of the H X MoO 3 samples (Figure 4b). For all the products, an intense peak at 530.5 eV was attributed to the MoO group 46. A peak at 532.3 eV in 6 h‐H X MoO 3 suggested the formation of the peroxo group47 and this peak disappeared as the reaction time increased.…”
Section: Figurementioning
confidence: 96%
“…We take MoO 3 as an example. Kalantar‐Zadeh and co‐workers reported that the plasmon resonance wavelengths of 2D H x MoO 3 nanodisks can be tuned in the range from visible to near‐infrared by intercalated H + concentration . H doping not only reduces the Mo oxidation state, but also induces a large number of free electrons.…”
Section: Electromagnetic Responsesmentioning
confidence: 99%